2022
DOI: 10.1007/s11846-022-00579-9
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate social performance improve bank efficiency? Evidence from European banks

Abstract: This paper analyses the impact of corporate social performance (CSP) on bank efficiency in a sample of 108 European listed banks across 21 countries over the period 2011–2019. Simar and Wilson’s two-stage approach (Simar and Wilson in J Econom 136:31–64, 2007) has been applied, specifically using data envelopment analysis (DEA) at the first stage to estimate efficiency scores and then truncated regression estimation with double-bootstrap to test the significance of the relationship between bank efficiency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 84 publications
6
13
0
Order By: Relevance
“…Regarding the effectiveness of systems and processes aimed at implementing best corporate governance practices, Nollet et al (2016) confirmed a U‐shaped relationship with various accounting performance measures. This finding aligns with studies examining their impact on efficiency in both the financial sector, particularly banking (López‐Penabad et al, 2022), and the EAE aspects of industrial companies (Ren et al, 2022).…”
Section: Theoretical Framework and Hypothesis Developmentsupporting
confidence: 88%
See 4 more Smart Citations
“…Regarding the effectiveness of systems and processes aimed at implementing best corporate governance practices, Nollet et al (2016) confirmed a U‐shaped relationship with various accounting performance measures. This finding aligns with studies examining their impact on efficiency in both the financial sector, particularly banking (López‐Penabad et al, 2022), and the EAE aspects of industrial companies (Ren et al, 2022).…”
Section: Theoretical Framework and Hypothesis Developmentsupporting
confidence: 88%
“…This relationship has been confirmed by Nollet et al (2016) for Standard & Poor's (S&P) listed companies, where, in the short term, profitability decreases as CSR activity increases, and in the long term, profitability rises. This metatheory has also been established in papers on specific sectors, such as Wang et al (2016) in construction, Franco et al (2020) in hospitality, and López‐Penabad et al (2022) in the financial sector. The same conclusion has been reached in multi‐sector studies conducted in contrasting geographical contexts such as India (Maqbool & Bakr, 2019) and Germany (Nuber et al, 2020).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 85%
See 3 more Smart Citations